Legal Protection Against Women Victims of Sexual Harassment Through Social Media (Cyberporn) - Choirunnisa, Sutiani (The Indonesian Journal of International Clinical Legal Education, 2021)
guarantee of protection and discrimination against women in Indonesia as contained in various international regulations including the Universal Declaration of Human Rights in 1948, then the International Covenant on Civil Rights. and Political Rights 1966, International Covenant on Economic, Social & Cultural Rights 1966, Convention on the Elimination of all Forms of Discrimination Against Women (CEDAW, Convention on the Elimination of All Forms of Discrimination against Women) in 1979, the Vienna Declaration (1986), the Declaration on the Elimination of Violence Against Women in 1994, and the most monumental is the Beijing Declaration and Platform for Action (1995). The purpose of this study is to analyze the legal protection for women victims of sexual harassment through social media (cyberpron).